(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2015)
This study attempted to explain the improvement of students’ reading comprehension in terms of precise information about the text pertaining to the text’s key ideas and order of facts, as well as creative reading of the text pertaining to the text’s characters and conclusion. To explain the improvement, the researcher employed classroom action research (CAR), which was carried out in two cycles of four meetings each. This investigation was conducted with the second-grade students of SMAN 1 Bontomarannu, a total of 35 individuals. According to the research findings, the adoption of the SMAN 1 Bontomarannu) Strategy significantly improved the students’ reading comprehension in terms of particular information and creative text interpretation. It was demonstrated by the cycle I mean score of 60.69. It was deemed acceptable, then upgraded to 73.38. In cycle II, it was evaluated as satisfactory. They are greater than the diagnostic test’s mean score of 50.7, which is considered inadequate. Therefore, the students’ reading comprehension improved in terms of precise knowledge about the text pertaining to primary concepts and order of details, as well as creative reading of the text pertaining to character and conclusion.